2011
DOI: 10.1590/s0100-69162011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Deposição de calda pulverizada na cultura da soja promovida pela aplicação aérea e terrestre

Abstract: RESUMO:Este trabalho teve como objetivo avaliar o efeito da tecnologia de aplicação aérea e terrestre de fitossanitários na deposição de calda, na cultura da soja. Avaliou-se, após a aplicação de um traçador, a deposição nas partes inferior e superior do dossel da cultura, por meio de espectrofotometria. O ensaio foi conduzido no delineamento em blocos ao acaso, com quatro repetições e oito tratamentos (formas de aplicação): 1 -Terrestre (Ponta de jato PALAVRAS-CHAVE: tecnologia de aplicação, aviação agrícola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 11 publications
3
20
0
8
Order By: Relevance
“…In the target kit ® system, spray hydraulic circuit nozzles are set in a bar and dragged on the crop, assuming greater coverage of the lower leaves of soybean, where the infection of diseases starts, as claimed by ALMEIDA et al (2005), CALLA et al (2009), REIS et al (2010) and CUNHA et al (2011. Since the motion of most fungicides is acropetal (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011 andLENZ et al 2011), spraying the base of plants suggests significantly a more effective control of the diseases when compared to sprayings by tips distant from the apex of soybean plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the target kit ® system, spray hydraulic circuit nozzles are set in a bar and dragged on the crop, assuming greater coverage of the lower leaves of soybean, where the infection of diseases starts, as claimed by ALMEIDA et al (2005), CALLA et al (2009), REIS et al (2010) and CUNHA et al (2011. Since the motion of most fungicides is acropetal (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011 andLENZ et al 2011), spraying the base of plants suggests significantly a more effective control of the diseases when compared to sprayings by tips distant from the apex of soybean plants.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the lower third of plant presents ideal environmental conditions since it keeps the leaf wetness for a longer period of time. Likewise, it is here that the coverage and penetration of the fungicide are more adversely affected by the leaf weight of tops to form a barrier spraying, favoring the pathogen (ALMEIDA et al 2,005;CALLA et al 2,009;REIS et al, 2010;CUNHA et al, 2011). Like most systemic fungicides suitable for chemical control of soybean foliar diseases move in the direction of the base to the apex of the plant, the leaves of the lower third of the plant become the target of spraying (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011;LENZ et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the decrease in deposition caused by chemigation is not proportional to the increase in water volume. Cunha et al (2011) evaluated the effect of ground and aerial applications on fungicide deposition into soybean canopies. This study found that there is no direct relationship between spray volume and deposition.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Cunha et al (2011) a tecnologia de aplicação é importante ferramenta para maximizar a produtividade quando esta é usada de forma correta. Para Repke e Teixeira (2013), a qualidade das aplicações tem sido principal fator do não sucesso das aplicações de agroquímicos, ou seja, há fatores que afetam esta qualidade de pulverização como clima, hospedeiro, alvo biológico, ingrediente ativo e veículo para o preparo de calda.…”
Section: Tecnologia De Aplicação De Agroquímicosunclassified